Analysis of the Students' Needs in General English Course at the Civil Engineering Study Program of a Higher Education in Papua - Tenri Ugi Irianto; Firman Firman (STAI Hubbulwathan Duri, 2023)
The goal of this study is to identify the requirements of students enrolled in the Civil Engineering Study Programme at a Papua university's General English Course during the second semester. A quantitative approach was taken for this investigation. Up to 200 students will participate in this survey. Questionnaire surveys were used to compile the data. Using a quantitative approach, the collected data is poured into a tabular data and matrix format for analysis. The findings show that raising students' consciousness of the importance of self-discipline in the classroom is a top priority. They must also participate actively in class in order to succeed. Students require content integration, English skills, and language aspects pertinent to course themes. In order to successfully complete the General English Course, students must have a firm grasp of all facets of the English language. In the framework of a General English Course, students will find the most success with the Student-Centred Learning Approach. Strategies like this include autonomy, curiosity, and self-control. Students have access to a wide variety of resources, including but not limited to those relating to civil engineering, general context, science and technology, and topics related to students' daily lives.